Study of the Effect of Nutrition-Rich Products on the Human Body - Aliqulova Diloram Abduraxmonovna; Mamayusupov Sherzod Alisher oglu (Genius Journals, 2022)
One of the problems that worries modern people today is non-communicable diseases caused by inactivity and malnutrition. In this study, an attempt was made to find a simple solution to this problem. It is said that various legumes and legumes can be used to slowly eradicate non-communicable diseases.
Keywords: Non-Infectious; Sedentary Lifestyle,; Dietary Fiber; Wheat Bran